Production of tilapia fish gelatin nanoparticles - Ibrahim Ali, Noorbatcha; Jaswir, Irwandi; Al-Khatib, Ma'an Fahmi Rashid (2015)
Gelatin is a very versatile natural biopolymer. It has more advantages such as biocompatibility, low cost, and biodegradability. Due to these advantages led to its application in the synthesis nanoparticles for drug delivery during the last decade. However due to tendency of inter-particle aggregation, stability of nanoparticles remains a big challenge and transient to be easily captured and analyzed. Mainly, the current major raw materials for gelatin nanoparticles production are from mammalian skins and bones (either bovine or porcine). Based on ethical, religious and health reasons, the use of mammalian-derived gelatins in various food and non-food products are main issue that criticism by Muslim, Jews, vegetarians and other religious communities. In this regard, fish gelatin nanoparticle has been highlighted as a better alternative to mammalian gelatins nanoparticles. Tilapia fish gelatin fabricated into nanoparticles using two-step desolvation method which involved the use of glutaraldehyde as crosslinking agent. Zeta sizer nano, FT-IR and FESEM was used for nanoparticles characterization. Fish gelatin has been successfully produced, in a size range between 100 nm and 200 nm. According to the infrared spectra, molecular bond of fish gelatin were similar to molecular bond of fish gelatin nanoparticles. The success of this research will be contributed in producing of halal drug.